More hours, more jobs? The employment effects of longer working hours - Martyn J. Andrews; Hans-Dieter Gerner; Thorsten Schank; Richard Upward (Institute for the Study of Labor (IZA), 2012)
Increases in standard hours have been a contentious policy issue in Germany. Whilst this might directly lead to a substitution of workers by hours, there may also be a positive employment effect due to reduced costs. Moreover, the response of firms differs between firms which offer overtime and those which do not. For a panel of German plants (2001-2006), we analyse the effect of increased standard hours on employment. Using difference-in-difference methods we find that, consistent with theory, overtime plants showed a significant positive employment response, whilst for standard-time plants there is no difference at all between plants which increased standard hours and those which did not.
Keywords: C23; J23; J81; 330; working time; employment; plant-level data; difference-in-differences; Arbeitszeitgestaltung; Überstunden; Beschäftigungseffekt; Deutschland